The Effect of Using Microsoft Teams on the Achievement and Self-Learning Skills among Undergraduate Students in the School of Educational Sciences at the University of Jordan - Al-Shboul, Muhannad (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The study aimed to investigate the effect of using Microsoft Teams on the achievement and self-learning skills among undergraduate students in the School of Educational Sciences at the University of Jordan. The study used the quasi-experimental approach, and the number of study members was (88) students of the Computerized Children’s Programs course, who were divided into two groups. They were intentionally chosen and randomly distributed. The first one was the experimental group that underwent teaching using the Microsoft Teams application, with (46) students; the second one was the control group that underwent teaching using the traditional method, with (42) students, during the first semester of 2022/2023. An achievement test consisting of (25) questions was prepared, as well as a self-learning skills scale consisting of (30) items. Both study tools were applied to the sample and their validity and reliability were verified. The results showed that there were statistically significant differences between the average scores of students in the achievement test and the self-learning scale post measurement, which was attributed to the teaching method variable and in favor of the experimental group that used the Microsoft Teams application. The study recommended implementing teaching methods using the Microsoft Teams application in the event of remote learning and to employ in the rest of the other educational courses and at all levels, editing courses to fit with the use of the Microsoft Teams application.